Pengembangan Media Pembelajaran Berbasis Augmented Reality Pada Pembelajaran Geografi Materi Siklus Hidrologi Kelas X SMA - Raharja, Azhar Mada; Suharto, Yusuf (Jayapangus Press, 2024)
The difficulty of students in understanding abstract and complex hydrological cycle material is caused by the limitations of technology-based learning media. There is also an impact caused by the era of the industrial revolution 4.0 in the aspect of creativity in the world of education is increasing so that teachers play an active role in developing learning media. This study aims to determine the effectiveness of the use of augmented reality-based learning media on the hydrological cycle material of geography subjects. This research method uses the Research and Development (R&D) method with the ADDIE research design model. The results of the analysis show that the average value of the effectiveness of the use of augmented reality-based learning media according to the material expert validator is 95% and the media expert is 87%, then also from student respondents, namely 91.36%, and teacher respondents 89.4% of the 4 assessments are included in the very high criteria from the other four criteria, namely high, low, and very low. Based on the results of the research analysis, it can be concluded that the effectiveness of the use of AR-based learning media on the Hydrological Cycle material of Geography Subjects in class X of SMA, the majority of these indicators have very high criteria. So the development of this learning media has high effectiveness and is able to stimulate the learning process of students. The majority of students also have no difficulty in using it.